A cacophony of cytokines explains the biopsychosocial interaction model of mental and physical disease - James A Morris (Archives of Depression and Anxiety - Peertechz Publications, 2018)
Social, psychological and biological factors interact to cause both mental and physical disease. Chronic low grade infl ammation is a risk factor for many conditions including atherosclerosis and its complications, type 2 diabetes mellitus, obesity and depression. The infl ammatory response is designed to protect against pathogenic micro-organisms but in the process some damage to our own tissues is inevitable. The process is complicated and is orchestrated by cytokines (intercellular messengers). Adaptive physiological responses to the many stresses of everyday life are also orchestrated by cytokines. The responses are nuanced and each variation involves a different specifi c tune. But if the response to stress runs at the same time as the infl ammatory response there will be a cacophony. The infl ammatory response will be sub-optimal increasing tissue damage and the physiological response to stress will be sub-optimal converting normal emotions into pathological mental states. Sleep, pregnancy and appetite control are also complex physiological states orchestrated by cytokines. They will be sub-optimal in the presence of chronic infl ammation. Infl ammation can be overt as in dental caries and periodontitis, or covert as in the carriage of bacterial pathogens such as Staphylococcus aureus within an epithelial surface. We must seek to modify the bacterial fl ora in order to prevent disease. It is suggested that the natural substance with most potential for achieving this aim is yoghurt.